New Contact Probe and Method to Measure Electrical Resistances in Battery Electrodes. Issue 12 (25th August 2016) - Mainusch, Nils; Christ, Torge; Siedenburg, Thammo; O'Donnell, Tom; Lutansieto, Meylia; Brand, Peter‐Jochen; Papenburg, Gerhard; Harms, Nina; Temel, Bilal; Garnweitner, Georg; Viöl, Wolfgang
Abstract: Electrical resistivity is an important measure to qualify electrodes for lithium‐ion batteries. A reliable determination of conductivity is of high practical importance with regard to, for example, electrode production improvements and quality control. To complement state‐of‐the‐art measuring techniques, a new method has been developed based on a new "micron‐powder probe". Following a simple measuring procedure, the system allows nondestructive, highly reproducible, and rapid data acquisition. In this paper, we describe the new concept thoroughly and present experimental results. These results demonstrate that an initial determination of resistance values in battery electrodes is beneficial especially if it is combined with an electrical postmortem analysis of cycled cathode disks. The outcome of our investigation is validated with regard to the electrochemical performance of cathodes in half‐cells. Abstract : Improved conductivity analysis : A new measuring system to analyze electrical conductivity is developed. The main component is a micron‐particle‐based "powder probe". The probe allows the nondestructive and excellent contacting of delicate surfaces. Applied for electrodes for lithium‐ion batteries, highly reproducible and fast data acquisition of bulk resistivity is possible.